Impact of biochar and manure application on in situ carbon dioxide flux, microbial activity, and carbon budget in degraded cropland soil of southern India. (16th March 2022) - Seki, Mayuko; Sugihara, Soh; Miyazaki, Hidetoshi; Jegadeesan, Muniandi; Kannan, Pandian; Bertrand, Isabelle; Tanaka, Haruo
Abstract: Biochar application is attracting attention to be an effective soil organic carbon (SOC) management to prevent land degradation, though quantitative information of its effect on carbon dioxide (CO2 ) flux and associated microbial responses is still scarce, especially in degraded tropical agroecosystems. We conducted a 27‐month field experiment with periodically measuring environmental factors, CO2 efflux rate, microbial biomass C (MBC), and SOC stock, and evaluated the impact of land management (control (C), biochar (B; 8.2 Mg C ha −1 ), farmyard manure (FYM) (M; 1.1 Mg C ha −1 yr −1 ), and a mixture of both (BM) on CO2 flux, microbial responses (MBC and qCO2 as microbial activity) and C budget, in tropical alkaline cropland of southern India. Based on the relationship between the CO2 efflux rate and environmental factors, cumulative CO2 flux was estimated at 2.4, 2.7, 4.0, and 3.7 Mg C ha −1 in the C, B, M, and BM treatments, respectively. Biochar application increased soil moisture though did not affect CO2 flux, causing a positive C budget (6.7 Mg C ha −1 ), because of the limited response of microbes to increased soil moisture due to the small amount of SOC. Biochar and FYM combined application did not increase CO2 flux compared with FYM alone, contributing to the largest SOC increment (8.9 Mg C ha −1 ) with a positive C budget (9.1 Mg C ha −1 ), due to little difference of microbial responses between the two treatments. Hence, biochar application combined with FYM could be an effective SOC management in the degraded cropland of southern India.